A supramolecular look at microenvironmental regulation of limbal epithelial stem cells and the differentiation of their progeny - Aldrovani, Marcela [UNESP] (2017)
Various approaches have been taken to improve our knowledge of the microenvironmental regulation of limbal epithelial stem cells. Researchers have extensively investigated the roles of growth factors, survival factors, cytokines, enzymes, and permeable molecules secreted by the limbal cells. However, recent evidence suggests that stem cell fate (i.e., self-renewal or differentiation) can also be influenced by biophysical and mechanical cues related to the supramolecular organization and the liquid crystalline (mesophase) nature of the stromal extracellular matrix. These cues can be sensed by stem cells and transduced into intracellular biochemical and functional responses, a process known as mechanotransduction. The objective of this review is to offer perspectives on the supramolecular microenvironmental regulation of limbal epithelial stem cells and the differentiation of their progeny.